Rotational flap technique for a sizable lesion of the temple - Laura Miccio; Marco May Lee (PAGEPress Publications, 2024)
A 50-year-old woman presented with a 2 cm large lesion on her right temple. A clinical diagnosis of partially pigmented basal cell carcinoma was established, leading to the planning of a subsequent excision.